Evidence-Based Perioperative Medicine comes of age: the Perioperative Quality Initiative (POQI). Issue 1 (December 2016) - Miller, Timothy; Shaw, Andrew; Mythen, Michael; Gan, Tong
Abstract The 1st POQI Consensus Conference occurred in Durham, NC, on March 4–5, 2016, and was supported by the American Society of Enhanced Recovery (ASER) and Evidence-Based Perioperative Medicine (EBPOM). The conference focused on enhanced recovery for colorectal surgery and discussed four topics—perioperative analgesia, perioperative fluid management, preventing nosocomial infection, and measurement and quality in enhanced recovery pathways.